Development and validation of the Japanese version of the Auckland individualism and collectivism scale: relationship between individualism/collectivism and mental health - Noda, Shota; Okawa, Sho; Kasch, Chantal; Vogelbacher, Christoph; Lindsay, Cameron E.; Nishiuchi, Motohiro; Kobayashi, Maaya; Hofmann, Stefan G. (Frontiers in Psychology, 2024)
Background: This study developed the Japanese version of the Auckland Individualism and Collectivism Scale (J-AICS), examined its reliability and validity, and explored the associations between its factors (compete, unique, responsibility, advice, and harmony) along with variables related to mental health in the Japanese population. Methods: We recruited 476 Japanese participants from the general population. Participants completed the J-AICS along with questionnaires pertaining to culture and mental health. Results: Confirmatory factor analysis indicated the correlated five-factor model showed a good fit to the data. The Cronbach's α and McDonald's ω coefficients were high for the individualism, collectivism, compete, unique, and advice factors, but low for the responsibility and harmony factors. Convergent validity was supported by significant relationships between culture-related variables. A one-way analysis of variance revealed the low individualism/collectivism cluster had higher loneliness and lower satisfaction with life than the high individualism and collectivism clusters. The multiple regression analyses showed that the responsibility factor was significantly and negatively associated with mental health concerning anxiety and depressive symptoms, loneliness, and satisfaction with life. In addition, the harmony factor was significantly and positively associated with the mental health. Conclusion: These findings demonstrate sufficient validity of the J-AICS; however, reliability was insufficient for responsibility and harmony. Further, responsibility was positively associated with mental health and harmony was negatively associated with mental health.